Investigate the Durability and Structure Integrity of Recycled Aggregate Concrete Beam Over Time: A Literature Review - Abdulmajed, Dalia Alaa Aldeen; Daud, Sultan Ahmed; Alrshoudi, Fahed (Al-Nahrain Journal for Engineering Sciences, 2024)
In term of sustainable practices, recycling plays a crucial role, particularly in the construction industry where the disposal of old structures generates significant waste. Recycling old concrete not only reduces the need for new natural resources but also eliminate waste accumulation. Numerous research study the behaviors of recycled aggregate concretes, practically focusing on the long term behaviours. A large number of studies have demonstrated that concrete made from recycled aggregate exhibits poorer long-term characteristics in comparison to aggregate from nature concrete. The long-term behaviour can be affected by three factor which is creep, shrinkage and tension stiffening. Greater management of these variables can enhance the RAC's long-term properties. The review will specifically focus on the influence of time dependent parameters i.e., creep, shrinkage, and loss of tension stiffening with time. Furthermore, it will explore the long-term deflection predicted from code used for deflection prediction, considering three codes: ACI, EC2, and the CSA code. The purpose of this paper is to enhance the understanding of long-term deflection of recycled aggregate concrete beam and evaluate the effectiveness of various factors that impact their structural performance.